2001
DOI: 10.1073/pnas.071058398
|View full text |Cite
|
Sign up to set email alerts
|

Human single-chain Fv intrabodies counteract in situ huntingtin aggregation in cellular models of Huntington's disease

Abstract: This investigation was pursued to test the use of intracellular antibodies (intrabodies) as a means of blocking the pathogenesis of Huntington's disease (HD). HD is characterized by abnormally elongated polyglutamine near the N terminus of the huntingtin protein, which induces pathological protein-protein interactions and aggregate formation by huntingtin or its exon 1-containing fragments. Selection from a large human phage display library yielded a single-chain Fv (sFv) antibody specific for the 17 Nterminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
134
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(141 citation statements)
references
References 34 publications
5
134
1
1
Order By: Relevance
“…It is notable that true nuclear aggregates of htt are not usually seen in this cell system (Ϸ1% of the cells have clearly visible EGFP-labeled aggregates in the nucleus). A similar observation has been made for other tagged htt constructs expressed in 293 cells (18,26,34,35) and in PC12 cells (E. Schweitzer, personal communication). One explanation for this observation is that the rapid cell death caused by the expanded repeat construct does not allow time for aggregates to form in the nucleus, yielding instead the large aggregates seen in Fig.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…It is notable that true nuclear aggregates of htt are not usually seen in this cell system (Ϸ1% of the cells have clearly visible EGFP-labeled aggregates in the nucleus). A similar observation has been made for other tagged htt constructs expressed in 293 cells (18,26,34,35) and in PC12 cells (E. Schweitzer, personal communication). One explanation for this observation is that the rapid cell death caused by the expanded repeat construct does not allow time for aggregates to form in the nucleus, yielding instead the large aggregates seen in Fig.…”
Section: Discussionmentioning
confidence: 54%
“…Biochemical assays show that WM7 coexpression also strongly inhibits htt aggregation. A recent study of this type showed that intracellular expression of a mAb against the N terminus of htt also inhibits aggregate formation induced in cultured cells by mutant htt exon 1 (26). The latter paper did not, however, report the effects of this scFv on cell survival, and the connection between aggregates and toxicity remains controversial.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Intracellularly expressed antibodies with specificity for htt have been shown to reduce aggregation and toxicity in cellular and organotypic slice culture models of HD (1)(2)(3)(4). However, high intracellular antibody (intrabody) expression levels have been required to obtain moderate reductions in aggregation and toxicity.…”
mentioning
confidence: 99%
“…These include small peptides binding to the poly(Q) stretch (17,25,41), intrabodies against the poly(Q) proteins (42,43), molecular chaperones targeting the misfolded proteins (32,44,45), and small chemical compounds inhibiting poly(Q) aggregation (29, 46 -48). However, none of these inhibitors have been shown to inhibit poly(Q) oligomer formation in cells except for QBP1, as shown in this study.…”
Section: Discussionmentioning
confidence: 99%